2020
DOI: 10.1007/978-3-030-53294-9_50
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Inclusive Educational Technology in Language Classrooms and Learner Perspectives: A Study of Nine Learner Narratives

Abstract: Emerging from studies of innovative educational-technology designs for disabled students, Universal Design for Learning (UDL) has established principles to bridge special needs education and regular classroom teaching. Although UDL has been around for some 40 years, apparently, only one empirical UDL study of language classrooms exists before Kasch, and no studies before him in lower-secondary language classrooms. Only Kasch has worked on integrating Computer-Assisted Language Learning and UDL in a pedagogical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…However, deeming from the above searches appears, Universal Design and SEN-pedagogy appears to be largely understudied. Further, although the literature seems to be keenly aware that there are potentials of E-learning and Universal Design and adaptable accessibility, very few empirical studies appear to address Universal Design in E-learning (Kasch, , 2020. In computer-assisted language learning, studies by are thus found which test the viability of Universal Design and computer-assisted language learning.…”
Section: Literature Review and State Of The Artmentioning
confidence: 99%
“…However, deeming from the above searches appears, Universal Design and SEN-pedagogy appears to be largely understudied. Further, although the literature seems to be keenly aware that there are potentials of E-learning and Universal Design and adaptable accessibility, very few empirical studies appear to address Universal Design in E-learning (Kasch, , 2020. In computer-assisted language learning, studies by are thus found which test the viability of Universal Design and computer-assisted language learning.…”
Section: Literature Review and State Of The Artmentioning
confidence: 99%
“…Additionally, platform Bookbuilder created by CAST allow to make content in multiple formats (text, images, audio and videos) at the same time. This platform has used in different empirical studies with optimal results (Kasch, 2019, 2020; Proctor, Dalton, & Grisham, 2007).…”
Section: Teaching Foreign Languages Online To Special Educational Nee...mentioning
confidence: 99%
“…Previous studies have shown how technology has helped language learners find their prospects and overcome various issues and quandaries (Darling-Aduana & Heinrich, 2018;Kasch, 2019;Pacheco et al, 2017). Due to its flexibility, the flipped classroom model has become one of the latest trends in English teaching and learning practices that cater to learners of different needs and conditions.…”
Section: Introductionmentioning
confidence: 99%